/- Copyright (c) 2022 David Kurniadi Angdinata. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: David Kurniadi Angdinata -/ import field_theory.splitting_field /-! # Cubics and discriminants This file defines cubic polynomials over a semiring and their discriminants over a splitting field. ## Main definitions * `cubic`: the structure representing a cubic polynomial. * `disc`: the discriminant of a cubic polynomial. ## Main statements * `disc_ne_zero_iff_roots_nodup`: the cubic discriminant is not equal to zero if and only if the cubic has no duplicate roots. ## References * https://en.wikipedia.org/wiki/Cubic_equation * https://en.wikipedia.org/wiki/Discriminant ## Tags cubic, discriminant, polynomial, root -/ noncomputable theory /-- The structure representing a cubic polynomial. -/ @[ext] structure cubic (R : Type*) := (a b c d : R) namespace cubic open cubic polynomial open_locale polynomial variables {R S F K : Type*} instance [inhabited R] : inhabited (cubic R) := ⟨⟨default, default, default, default⟩⟩ instance [has_zero R] : has_zero (cubic R) := ⟨⟨0, 0, 0, 0⟩⟩ section basic variables {P : cubic R} [semiring R] /-- Convert a cubic polynomial to a polynomial. -/ def to_poly (P : cubic R) : R[X] := C P.a * X ^ 3 + C P.b * X ^ 2 + C P.c * X + C P.d /-! ### Coefficients -/ section coeff private lemma coeffs : (∀ n > 3, P.to_poly.coeff n = 0) ∧ P.to_poly.coeff 3 = P.a ∧ P.to_poly.coeff 2 = P.b ∧ P.to_poly.coeff 1 = P.c ∧ P.to_poly.coeff 0 = P.d := begin simp only [to_poly, coeff_add, coeff_C, coeff_C_mul_X, coeff_C_mul_X_pow], norm_num, intros n hn, repeat { rw [if_neg] }, any_goals { linarith only [hn] }, repeat { rw [zero_add] } end @[simp] lemma coeff_gt_three (n : ℕ) (hn : 3 < n) : P.to_poly.coeff n = 0 := coeffs.1 n hn @[simp] lemma coeff_three : P.to_poly.coeff 3 = P.a := coeffs.2.1 @[simp] lemma coeff_two : P.to_poly.coeff 2 = P.b := coeffs.2.2.1 @[simp] lemma coeff_one : P.to_poly.coeff 1 = P.c := coeffs.2.2.2.1 @[simp] lemma coeff_zero : P.to_poly.coeff 0 = P.d := coeffs.2.2.2.2 lemma a_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.a = Q.a := by rw [← coeff_three, h, coeff_three] lemma b_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.b = Q.b := by rw [← coeff_two, h, coeff_two] lemma c_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.c = Q.c := by rw [← coeff_one, h, coeff_one] lemma d_of_eq {Q : cubic R} (h : P.to_poly = Q.to_poly) : P.d = Q.d := by rw [← coeff_zero, h, coeff_zero] @[simp] lemma to_poly_injective (P Q : cubic R) : P.to_poly = Q.to_poly ↔ P = Q := ⟨λ h, cubic.ext _ _ (a_of_eq h) (b_of_eq h) (c_of_eq h) (d_of_eq h), congr_arg _⟩ @[simp] lemma of_a_eq_zero (ha : P.a = 0) : P.to_poly = C P.b * X ^ 2 + C P.c * X + C P.d := by rw [to_poly, C_eq_zero.mpr ha, zero_mul, zero_add] @[simp] lemma of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) : P.to_poly = C P.c * X + C P.d := by rw [of_a_eq_zero ha, C_eq_zero.mpr hb, zero_mul, zero_add] @[simp] lemma of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) : P.to_poly = C P.d := by rw [of_a_b_eq_zero ha hb, C_eq_zero.mpr hc, zero_mul, zero_add] @[simp] lemma of_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d = 0) : P.to_poly = 0 := by rw [of_a_b_c_eq_zero ha hb hc, C_eq_zero.mpr hd] @[simp] lemma zero : (0 : cubic R).to_poly = 0 := of_zero rfl rfl rfl rfl @[simp] lemma eq_zero_iff : P.to_poly = 0 ↔ P = 0 := by rw [← zero, to_poly_injective] lemma ne_zero (h0 : ¬P.a = 0 ∨ ¬P.b = 0 ∨ ¬P.c = 0 ∨ ¬P.d = 0) : P.to_poly ≠ 0 := by { contrapose! h0, rw [eq_zero_iff.mp h0], exact ⟨rfl, rfl, rfl, rfl⟩ } lemma ne_zero_of_a_ne_zero (ha : P.a ≠ 0) : P.to_poly ≠ 0 := (or_imp_distrib.mp ne_zero).1 ha lemma ne_zero_of_b_ne_zero (hb : P.b ≠ 0) : P.to_poly ≠ 0 := (or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).1 hb lemma ne_zero_of_c_ne_zero (hc : P.c ≠ 0) : P.to_poly ≠ 0 := (or_imp_distrib.mp (or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).2).1 hc lemma ne_zero_of_d_ne_zero (hd : P.d ≠ 0) : P.to_poly ≠ 0 := (or_imp_distrib.mp (or_imp_distrib.mp (or_imp_distrib.mp ne_zero).2).2).2 hd end coeff /-! ### Degrees -/ section degree /-- The equivalence between cubic polynomials and polynomials of degree at most three. -/ @[simps] def equiv : cubic R ≃ {p : R[X] // p.degree ≤ 3} := { to_fun := λ P, ⟨P.to_poly, degree_cubic_le⟩, inv_fun := λ f, ⟨coeff f 3, coeff f 2, coeff f 1, coeff f 0⟩, left_inv := λ P, by ext; simp only [subtype.coe_mk, coeffs], right_inv := λ f, begin ext (_ | _ | _ | _ | n); simp only [subtype.coe_mk, coeffs], have h3 : 3 < n + 4 := by linarith only, rw [coeff_gt_three _ h3, (degree_le_iff_coeff_zero (f : R[X]) 3).mp f.2 _ $ with_bot.coe_lt_coe.mpr h3] end } lemma degree (ha : P.a ≠ 0) : P.to_poly.degree = 3 := degree_cubic ha lemma degree_of_a_eq_zero (ha : P.a = 0) (hb : P.b ≠ 0) : P.to_poly.degree = 2 := by rw [of_a_eq_zero ha, degree_quadratic hb] lemma degree_of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c ≠ 0) : P.to_poly.degree = 1 := by rw [of_a_b_eq_zero ha hb, degree_linear hc] lemma degree_of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d ≠ 0) : P.to_poly.degree = 0 := by rw [of_a_b_c_eq_zero ha hb hc, degree_C hd] lemma degree_of_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) (hd : P.d = 0) : P.to_poly.degree = ⊥ := by rw [of_zero ha hb hc hd, degree_zero] lemma leading_coeff (ha : P.a ≠ 0) : P.to_poly.leading_coeff = P.a := leading_coeff_cubic ha lemma leading_coeff_of_a_eq_zero (ha : P.a = 0) (hb : P.b ≠ 0) : P.to_poly.leading_coeff = P.b := by rw [of_a_eq_zero ha, leading_coeff_quadratic hb] lemma leading_coeff_of_a_b_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c ≠ 0) : P.to_poly.leading_coeff = P.c := by rw [of_a_b_eq_zero ha hb, leading_coeff_linear hc] lemma leading_coeff_of_a_b_c_eq_zero (ha : P.a = 0) (hb : P.b = 0) (hc : P.c = 0) : P.to_poly.leading_coeff = P.d := by rw [of_a_b_c_eq_zero ha hb hc, leading_coeff_C] end degree /-! ### Map across a homomorphism -/ section map variables [semiring S] {φ : R →+* S} /-- Map a cubic polynomial across a semiring homomorphism. -/ def map (φ : R →+* S) (P : cubic R) : cubic S := ⟨φ P.a, φ P.b, φ P.c, φ P.d⟩ lemma map_to_poly : (map φ P).to_poly = polynomial.map φ P.to_poly := by simp only [map, to_poly, map_C, map_X, polynomial.map_add, polynomial.map_mul, polynomial.map_pow] end map end basic section roots open multiset /-! ### Roots over an extension -/ section extension variables {P : cubic R} [comm_ring R] [comm_ring S] {φ : R →+* S} /-- The roots of a cubic polynomial. -/ def roots [is_domain R] (P : cubic R) : multiset R := P.to_poly.roots lemma map_roots [is_domain S] : (map φ P).roots = (polynomial.map φ P.to_poly).roots := by rw [roots, map_to_poly] theorem mem_roots_iff [is_domain R] (h0 : P.to_poly ≠ 0) (x : R) : x ∈ P.roots ↔ P.a * x ^ 3 + P.b * x ^ 2 + P.c * x + P.d = 0 := begin rw [roots, mem_roots h0, is_root, to_poly], simp only [eval_C, eval_X, eval_add, eval_mul, eval_pow] end theorem card_roots_le [is_domain R] [decidable_eq R] : P.roots.to_finset.card ≤ 3 := begin apply (to_finset_card_le P.to_poly.roots).trans, by_cases hP : P.to_poly = 0, { exact (card_roots' P.to_poly).trans (by { rw [hP, nat_degree_zero], exact zero_le 3 }) }, { exact with_bot.coe_le_coe.1 ((card_roots hP).trans degree_cubic_le) } end end extension variables {P : cubic F} [field F] [field K] {φ : F →+* K} {x y z : K} /-! ### Roots over a splitting field -/ section split theorem splits_iff_card_roots (ha : P.a ≠ 0) : splits φ P.to_poly ↔ (map φ P).roots.card = 3 := begin replace ha : (map φ P).a ≠ 0 := (ring_hom.map_ne_zero φ).mpr ha, nth_rewrite_lhs 0 [← ring_hom.id_comp φ], rw [roots, ← splits_map_iff, ← map_to_poly, splits_iff_card_roots, ← ((degree_eq_iff_nat_degree_eq $ ne_zero_of_a_ne_zero ha).mp $ degree ha : _ = 3)] end theorem splits_iff_roots_eq_three (ha : P.a ≠ 0) : splits φ P.to_poly ↔ ∃ x y z : K, (map φ P).roots = {x, y, z} := by rw [splits_iff_card_roots ha, card_eq_three] theorem eq_prod_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : (map φ P).to_poly = C (φ P.a) * (X - C x) * (X - C y) * (X - C z) := begin rw [map_to_poly, eq_prod_roots_of_splits $ (splits_iff_roots_eq_three ha).mpr $ exists.intro x $ exists.intro y $ exists.intro z h3, leading_coeff ha, ← map_roots, h3], change C (φ P.a) * ((X - C x) ::ₘ (X - C y) ::ₘ {X - C z}).prod = _, rw [prod_cons, prod_cons, prod_singleton, mul_assoc, mul_assoc] end theorem eq_sum_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : map φ P = ⟨φ P.a, φ P.a * -(x + y + z), φ P.a * (x * y + x * z + y * z), φ P.a * -(x * y * z)⟩ := begin apply_fun to_poly, any_goals { exact λ P Q, (to_poly_injective P Q).mp }, rw [eq_prod_three_roots ha h3, to_poly], simp only [C_neg, C_add, C_mul], ring1 end theorem b_eq_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : φ P.b = φ P.a * -(x + y + z) := by injection eq_sum_three_roots ha h3 theorem c_eq_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : φ P.c = φ P.a * (x * y + x * z + y * z) := by injection eq_sum_three_roots ha h3 theorem d_eq_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : φ P.d = φ P.a * -(x * y * z) := by injection eq_sum_three_roots ha h3 end split /-! ### Discriminant over a splitting field -/ section discriminant /-- The discriminant of a cubic polynomial. -/ def disc {R : Type*} [ring R] (P : cubic R) : R := P.b ^ 2 * P.c ^ 2 - 4 * P.a * P.c ^ 3 - 4 * P.b ^ 3 * P.d - 27 * P.a ^ 2 * P.d ^ 2 + 18 * P.a * P.b * P.c * P.d theorem disc_eq_prod_three_roots (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : φ P.disc = (φ P.a * φ P.a * (x - y) * (x - z) * (y - z)) ^ 2 := begin simp only [disc, ring_hom.map_add, ring_hom.map_sub, ring_hom.map_mul, map_pow], simp only [ring_hom.map_one, map_bit0, map_bit1], rw [b_eq_three_roots ha h3, c_eq_three_roots ha h3, d_eq_three_roots ha h3], ring1 end theorem disc_ne_zero_iff_roots_ne (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : P.disc ≠ 0 ↔ x ≠ y ∧ x ≠ z ∧ y ≠ z := begin rw [← ring_hom.map_ne_zero φ, disc_eq_prod_three_roots ha h3, pow_two], simp only [mul_ne_zero_iff, sub_ne_zero], rw [ring_hom.map_ne_zero], tautology end theorem disc_ne_zero_iff_roots_nodup (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) : P.disc ≠ 0 ↔ (map φ P).roots.nodup := begin rw [disc_ne_zero_iff_roots_ne ha h3, h3], change _ ↔ (x ::ₘ y ::ₘ {z}).nodup, rw [nodup_cons, nodup_cons, mem_cons, mem_singleton, mem_singleton], simp only [nodup_singleton], tautology end theorem card_roots_of_disc_ne_zero [decidable_eq K] (ha : P.a ≠ 0) (h3 : (map φ P).roots = {x, y, z}) (hd : P.disc ≠ 0) : (map φ P).roots.to_finset.card = 3 := begin rw [to_finset_card_of_nodup $ (disc_ne_zero_iff_roots_nodup ha h3).mp hd, ← splits_iff_card_roots ha, splits_iff_roots_eq_three ha], exact ⟨x, ⟨y, ⟨z, h3⟩⟩⟩ end end discriminant end roots end cubic